Evaluation of Long-Coronavirus Disease 2019 Cases Readmitted to Intensive Care Units Due to Acute Respiratory Failure: Point Prevalence Study - Eylem Tunçay; Özlem Moçin; Özlem Ediboğlu; Nalan Adıgüzel; Sinem Güngör; İnşa İşcanlı; Berrin Er; Nilgün Alptekinoğlu Mendil; Adnan Usalan; Didem Yılmaz; Hülya Keskin; Gül Erdal Dönmez; et al. (Thoracic Research and Practice)
OBJECTIVE: Coronavirus disease 2019 (COVID-19) caused morbidity and mortality worldwide. Besides the acute effects, subacute and long-term effects are defined as long-COVID causing morbidity. The intensive care unit (ICU) data of long-COVID-19 cases were evaluated with the participation of 11 centers.